Um panorama epidemiológico da dengue na última década na Amazônia - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
Dengue is a viral disease caused by four serotypes (DENV 1 - 4) transmitted by mosquitoes of the genus Aedes spp. which are favored in tropical and subtropical climates. The aim of this study was to analyze the epidemiological profile of dengue fever between 2014 and 2024 in the western region of the state of Pará, in the Brazilian Amazon. To do this, we used the official records of the National System of Notifiable Diseases, from the Department of Informatics of the SUS/Tabnet, as a source of information. Information was collected on confirmed cases, incidence rate, number of deaths, etc. The results showed that 4,792 confirmed cases were recorded, 74.5% of which occurred in the first few months of the year. Of these cases, 55.5% were female, and the 20-39 age group was the most representative, with 38.7% of cases. The brown race was the most affected, accounting for 79.7% of cases. The majority of cases (96.7%) progressed to a cure and were classified as dengues and classic dengue, with the DENV-2 serotype presenting the highest frequency. The findings point to the ongoing need for vector control and prevention strategies. In addition, scientific research is needed to verify behavioral changes and the evolution of dengue in different periods.
Keywords: Arbovirose; Epidemiologia; Saúde Pública; CNPQ:: CIÊNCIAS DA SAÚDE